Antigenic characterization of foot-and-mouth disease virus type O strains isolated from outbreaks in vaccinated herds - WANI, S A; AHUJA, K L; PRASAD, S; KUMAR, ARVIND (The Indian Journal of Animal Sciences, 2013)
The extent of antigenic relationship of foot-and-mouth-disease (FMD) virus field strains with reference to (vaccine) strain was assessed. Three type 0 field strains, isolated from outbreaks in vaccinated herds of different areas and periods, were selected. The isolates were characterized by sandwich-enzyme-linked immunosorbent assay (ELISA) and in vivo cross-protection tests in guineapigs. In one-way testing by sandwich ELISA, field isolates were reacted with anti-146S reference serum and the relationship was revealed by calculation ofr-values. In reverse direction testing, the reference strain was reacted with anti-146S sera against field isolates followed by calculation of r-values. The r-values obtained in both the directions were >0.25. This suggested a relationship of the reference strain with field isolates and vice versa. The reference strain gave 100% protection to guineapigs against challenge with all the 3 field isolates. This showed a good correlation between in vitro sandwich ELISA and in vivo cross-protection tests.